Performance Comparison of Controllers for Suppressing the Structural Building Vibration - Normaisharah Mamat; Fitri Yakub; Sheikh Ahmad Zaki Shaikh Salim; Mohamed Sukri Mat Ali (Institute of Advanced Engineering and Science, 2018)
This paper presents the modelling and simulation of controllers for controlling the position of two degree of freedom (2 DOF) mass spring damper system. Proportional integral (PI), fuzzy logic controller (FLC) and sliding mode controller (SMC) are design to minimize the vibration of the system that represent as building structure towards earthquake. A structural building is simulate based on real earthquake occur in El Centro on May 1940. The algorithm for building structure, actuator and controller is derived. Matlab/Simulink is used to analyze the performance of controllers towards the vibration building structure. At the end of the study the time response for two story building for uncontrolled and controlled system is present. Besides, the result for limitation voltage for each controller is also analyse to determine the maximum voltage consume for the system. The simulation results show the comparison of the controllers’ performance in suppressing the building vibration. From performance analysis, SMC provides better performance compared to PI and FLC based on structural vibration reduction.